A Modified Dura Puncture Procedure to Reduce Brain Shift in Deep Brain Stimulation Surgery: One Institution's Experience - Wu, Yu-Xi; Xiang, Wei; Wang, Jia-Jing; Liu, Xiao-Ming; Yi, Dong-Ye; Tian, Han; Zhao, Hong-Yang; Jiang, Xiao-Bing; Fu, Peng (Frontiers in Neurology, 2022)
Objective: The therapeutic effect of deep brain stimulation (DBS) surgery mainly depends on the accuracy of electrode placement and the reduction in brain shift. Among the standard procedures, cerebrospinal fluid (CSF) loss or pneumocephalus caused by dura incision is thought to be the main reason for brain shift and inaccuracy of electrode placement. In the current study, we described a modified dura puncture procedure to reduce brain shift and compared it with the general procedure of DBS surgery in terms of electrode placement accuracy. Materials and Methods: We retrospectively analysed a series of 132 patients who underwent DBS surgery in Wuhan Union Hospital from December 2015 to April 2021. According to the different surgery procedures, patients were classified into two cohorts: the dura incision group (DI cohort) had 49 patients receiving the general procedure, and a dura puncture group (DP cohort) had 83 patients receiving the modified procedure. Postoperative pneumocephalus volume and CSF loss volume, electrode fusion error, and trajectory number were calculated. Meanwhile, intraoperative electrophysiological signal length, electrode implantation duration and other parameters were analysed. Results: In the current study, we introduced an improved electrode implantation procedure for DBS surgery named the dura puncture procedure. Compared with the general DI cohort (n = 49), the modified DP cohort (n = 83) had a shorter electrode implantation duration (p < 0.0001), smaller postoperative pneumocephalus volume and lower CSF leakage volume (p < 0.0001), and smaller electrode fusion error (p < 0.0001). There was no significant difference in intraoperative electrophysiological signal length (p> 0.05) or adverse events (perioperative cerebral haematoma, skin erosion, epilepsy, p > 0.05) between the two cohorts. Conclusion: The dura puncture procedure is a modified procedure that can reduce brain shift and ensure implantation accuracy during deep brain stimulation surgery without adverse events.